Reading comprehension and learning strategies in elementary school: integrative literature review (Research, Society and Development, 2022)
This study aimed to identify and the reader is reading and use of the review of the learning strategies of Elementary School students. For this, an integrative analysis of the literature was carried out in the following sources: Scientific Electronic Library Online (SciELO); portal of electronic journals of Psychology (PePSIC) and Google Scholar (Google Scholar). Eleven articles were selected for analysis. According to the results, the students showed little ability to use learning strategies in their school tasks and had difficulty understanding the text read. Finally, it is emphasized that the reader understands it and its relationship with learning strategies in schools are essential for the development of educational policies and the improvement of teaching, so they are transversal to the education of history.